Knotted in-tube and mini-column solid phase extraction of polycyclic aromatic compounds and nitroaromatics from aqueous samples for their determination by gas chromatography–mass spectrometry. (25th July 2006) - Mishra, Sanjeev; Gupta, Manju; Jain, Archana; Verma, Krishna K.
The selectivity of in-tube extraction by PTFE tubing vis-a-vis mini-column SPE has been evaluated for preconcentration and cleanup of PACs in their natural matrix, and has been found to effectively remove many polar analytes such as nitrogen containing aromatic heterocyclic compounds, anilines, phenols and certain organophosphorus pesticides. Knitting of tubings created a secondary flow pattern that promoted radial diffusion and this has resulted in augmented retention of PACs. A rectilinear calibration graph was obtained for 1–100 µg L -1 of PACs by in-tube SPE, and 0.1–40 µg L -1 PACs and nitroaromatics by mini-column SPE of, respectively, 100 ml and 60 ml of aqueous sample. The detection limits were between 60 ng L -1 and 214 ng L -1 (TIC detection), and 9 ng L -1 and 60 ng L -1 (SIM detection), respectively, in GC-MS of extracts.